-1
$\begingroup$

I'm trying to prove a formula that is tautology without using truth tables and i'm stuck... Here is what i tried:

Formula: $((p \land q) \land(p \to r) \land (q \to r)) \to r$

What i did:

  1. $((p \land q) \land(p \to r) \land (q \to r)) \to r$
  2. $((p \land q) \land(\lnot p \lor r) \land (\lnot q \lor r)) \to r$
  3. $(\lnot p \land \lnot q) \lor (p \land \lnot r) \lor (q \lor \lnot r) \lor r$

And what should i do now ?

$\endgroup$
0
$\begingroup$

Try to make your formula false. To do it, $r$ shold be false (denote $r=0$ for short). But the predecessor should be true which means that all $p\wedge q$, $p\to r$ and $q\to r$ should be true. It is impossible because since $p\wedge q=1,$ then $p=1$ and $q=1$ and both implications $p\to r$, $q\to r$ are false.

I have shown that it is impossible to find a valuation for $p,q,r$ which makes our formula false.

$\endgroup$
0
$\begingroup$

You were a little quick going from:

  1. $((p \land q) \land(\lnot p \lor r) \land (\lnot q \lor r)) \to r$

to:

  1. $(\lnot p \land \lnot q) \lor (p \land \lnot r) \lor (q \lor \lnot r) \lor r$

And in fact you made some small mistakes ... so let's do that again:

  1. $((p \land q) \land(\lnot p \lor r) \land (\lnot q \lor r)) \to r \Leftrightarrow \text{ (Implication)}$

  2. $\neg ((p \land q) \land(\lnot p \lor r) \land (\lnot q \lor r)) \lor r \Leftrightarrow \text{ (DeMorgan)}$

  3. $\neg (p \land q) \lor \neg(\lnot p \lor r) \lor \neg(\lnot q \lor r)) \lor r \Leftrightarrow \text{ (DeMorgan x 3)}$

  4. $(\neg p \lor \neg q) \lor (p \land \neg r) \lor (q \land \neg r) \lor r $

So this is different from what you got! ... can you take it from here?

If not:

5. $(\neg p \lor \neg q) \lor (p \land \neg r) \lor (q \land \neg r) \lor r \Leftrightarrow \text{ (Association)}$
6. $\neg p \lor \neg q \lor (p \land \neg r) \lor (q \land \neg r) \lor r \Leftrightarrow \text{ (Commutation)}$
7. $\neg p \lor (p \land \neg r) \lor (q \land \neg r) \lor \neg q \lor r \Leftrightarrow \text{ (DeMorgan)}$
8. $\neg p \lor (p \land \neg r) \lor (q \land \neg r) \lor \neg (q \land \neg r) \Leftrightarrow \text{ (Complement)}$
9. $\neg p \lor (p \land \neg r) \lor \top \Leftrightarrow \text{ (Annihilation)}$
10. $\top$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.